Effect of individual and combined supplementation of vitamin E and selenium on the performance of broiler chicks fed ochratoxin - A - PRAKASH, K; UMAKANTHA, B; DEVEGOWDA, G; GOWDH, C V; KRISHNAPPA, G (The Indian Journal of Animal Sciences, 2013)
An experiment with a completely randomized block design was used to evaluate the effects of ochratoxin (2 mg/kg of diet), vitamin E (400 mg/kg) and selenium (1 mg/kg), both individually and in combination, in 6 week old broilers. Commercial broilers (240) were randomly placed in battery brooder with 10 birds/pen. Each treatment was replicated 3 times. A significant (P